Preparation and Quality Evalution of Amala (Phyllanthus emblica L.) Fruit Leather (NUTA Journal, 2020)
Preparation and quality evaluation of amala (Phyllanthus emblica L.) fruit leather from chakaiya variety was done. The amala pulp and sugar  were mixed separately at the proportion of 50:50, 65:35, 57.5:42.5, 80:20, and 72.5:27.5 to prepare leather and labeled as samples A, B, C, D and E respectively. Total soluble solids, acidity, pH, total ash, crude protein, crude fat, crude fiber, total sugar and vitamin C content of each product samples prepared were determined. For sensory analysis, 9-point hedonic rating test was carried out. Sensory evaluation showed that all the sensory attribute scores were significantly higher (P